2017
DOI: 10.1038/s41598-017-08478-w
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the stability and culturability of Chinese enterotypes

Abstract: Although many gut microbial enterotypes have been reported in Europe, Africa and the U.S., their effects on human health are still not yet clear. Culturing gut microbial enterotypes in vitro will be helpful to study their effects and applications. Here, fecal samples from 13 healthy Chinese volunteers were collected and subjected to next-generation sequencing. The results showed that seven of these samples belong to the Bacteroides enterotype and another six to the Prevotella enterotype. Stability of these Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 45 publications
2
17
0
1
Order By: Relevance
“…This study found that Tibetans and Uygurs both had significant difference in gut microbial composition, compared with Hans who were from Tibet or Xinjiang respectively. As shown in the genetic relationship, Tibetan and Uygur had great genetic distance to Han [ 15 , 34 ]. This could contribute to different bacterial colonization in the gut [ 15 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study found that Tibetans and Uygurs both had significant difference in gut microbial composition, compared with Hans who were from Tibet or Xinjiang respectively. As shown in the genetic relationship, Tibetan and Uygur had great genetic distance to Han [ 15 , 34 ]. This could contribute to different bacterial colonization in the gut [ 15 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The patient is recommended to initiate treatment as soon as a diagnosis is made. However, several studies have reported that the core ecosystem is stable in intervals of 1 year from the first sampling 80 – 83 . Taking the time it took for patients to be placed under treatment and the stability of the gut microbiota into consideration, a longitudinal study design conducted in a short time interval would not change our major findings.…”
Section: Discussionmentioning
confidence: 99%
“…Batch culture fermentation was carried out using the procedure described by Hu et al [19], Rycroft et al [20], and Lei et al [21]. The VI growth medium was adjusted to pH 6.5 with 1 M HCl, and starch (8 g/L) was prepared and added according to our previous studies [12,19,22]. The liquid culture media was autoclaved at 121˚C for 15 min and cooled to room temperature under anaerobic conditions (10% H 2 , 10% CO 2 , and 80% N 2 ).…”
Section: In Vitro Batch Culture Fermentationmentioning
confidence: 99%
“…Considering that the VI medium could simulate the human gut microbiota in vitro with higher than 80% similarity with the original fecal bacterial community [22], VI medium was used in this study. After fermentation in vitro, the high throughput sequencing results showed that the FLU2 samples were enriched for the microbial groups of Escherichia/Shigella, Ruminococcaceae UCG 014, and Sutterella.…”
Section: Plos Onementioning
confidence: 99%